Penentuan kenaikan level pada karyawan dengan penerapan metode profile matching - Lis Utari; Ika Merina (Sekolah Tinggi Ilmu Komputer Binaniaga, 2019)
PT Infomedia Solusi Humanika is an outsourcing company that works with PT. Telkom Indonesia, electing employees who will go up / level, but a few months later the level obtained by the employee dropped or decreased level because that will be held re-election for all employees in the Fulfillment division using the Profile Matching calculation (Matching Profile). In the Profile Matching Method, there is a Gap, that is, if the employee's value approaches the value of the gap, the employee's opportunity to level up is even greater. The criteria used for evaluating employee performance are Personal Data criteria, Job Performance criteria, Job Attitude criteria, and Behavior criteria. After analyzing using the Profile Matching method for 28 employees of PT. Infomedia Humanika Solutions obtained rankings and known to be the most superior employee among other employees. For data analysis calculations used Linear Regression analysis. The results of the analysis found that the criteria that had the most influence on employee ranking were the Job Performance criteria and the least influential criteria were the Work Attitude criteria.